Effect of CNTs addition on the erosive wear response of epoxy resin and carbon fibre composites. (May 2016) - Papadopoulos, A.; Gkikas, G.; Paipetis, A.S.; Barkoula, N.-M.
Abstract: In the current study we investigated the effect of carbon nanotubes (CNTs) addition on the erosive wear response of epoxy resin and carbon fibre reinforced laminates (CFRPs) and demonstrated the positive synergy of CNTs and carbon fibres, which resulted in almost 50% decrease of the erosion rate (ER) of the CFRPs at high impact angles (90°). Incorporation of CNTs led in slight increase of the ER of the epoxy systems, especially at low impact angles. The relative fibre orientation in the CFRPs had a negligible effect on the erosive wear response mainly due to the quasi isotropic nature of the tested CFRPs. Based on the erosion efficiency parameter the response of the epoxy systems was characterised as semi-brittle, while CFRPs behaved in a brittle manner. Scanning electron micrograph provided evidence that the presence of CNTs reduced the amount of broken and/or detached fibres in the case of CFRPs.